PARIWISATA RAMAH DISABILITAS DI WILAYAH JAKARTA - Jenal Abidin; Rahmat Darmawan; Revi Agustin Aisyianita (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
The purpose of this study is to determine the form of providing accessibility for tourists with disabilities in tourist locations in DKI Jakarta Province, especially the Kota Tua area where there is a tourist attraction for the Jakarta History Museum. Efforts to improve disability-friendly tourist destination services require systematic efforts from various parties. Jakarta as a big city and the national capital becomes a barometer of the view of a modern, egalitarian city. It provides fulfilment of its rights to the community following the Regulation of the Minister of Public Works Number 30 of 2006 concerning Technical Guidelines for Facilities and Accessibility in Buildings and the Environment, namely the primary size of space, pedestrian paths, guidelines, parking areas, ramps, and signs and markers. The research method used is descriptive qualitative research with data collection techniques using observation techniques, interviews and documents. The results showed that the condition of existing facilities and facilities at the tourist site, namely the Jakarta History Museum, has not standardized the feasibility according to the accessibility guidelines for people with disabilities, because some standard facilities are not sufficiently available, so it can be said that they are not yet accessible for accessibility and tourism facilities. Persons with disabilities at the Jakarta History Museum.